Active in Not Being Active (AINBA): how East Asian powers accept R2P. Issue 1 (2nd January 2018) - Bae, Sangmin; Infanzon, Amy; Abbe, Michael J.
ABSTRACT: This article explores and compares the positions of two major powers in East Asia—China and Japan—towards the 'Responsibility to Protect' (R2P) norm. R2P calls for collective international responsibility in the event that states are unwilling or unable to protect their people. Evaluating the mainstream argument in the literature that China and Japan have recently been welcoming the R2P norm, we ask the following questions: To what extent have China and Japan aligned themselves with R2P? How do international and national factors play out to influence their R2P stance? To summarize our findings up front: unlike what much of the current literature says, China and Japan's acceptance and practice of the R2P norm are largely pro forma. We argue that they both appear active in participating in the debates but only in order to remain inactive. In other words, they are active participants in the debates and discussions on R2P, but their aim is not to further its usage but to contain its effects. Their current stance on R2P is characterized by what we will call 'Active in Not Being Active' (AINBA). The article discusses the key sources and rationale for their AINBA policy with regard to R2P.